Robotically-driven orthoses exert proximal-to-distal differential recovery on the lower limbs in children with hemiplegia, early after acquired brain injury. (July 2018) - Beretta, Elena; Molteni, Erika; Biffi, Emilia; Morganti, Roberta; Avantaggiato, Paolo; Strazzer, Sandra
Abstract: Robotically-driven orthoses (RDO) are promising for treating gait impairment in children with hemiplegia after acquired brain injury (ABI). Despite this, existing literature on the employment of RDO in ABI is scanty, and cohorts' age spans throughout the adult age, with no specific focus on the developmental age. We aim to compare a treatment solely based on conventional physiotherapy (CP) with a program combining RDO training with CP, and to examine the effect of time following ABI on recovery. A prospective two-cohorts study was conducted in a rehabilitation hospital. Post-acute and chronic children with hemiplegia due to ABI underwent either: (i) 20 sessions of RDO plus 20 sessions of CP (n = 29), or (ii) 40 of CP (n = 12). Gross Motor Function Measures (GMFM), Functional Assessment Questionnaire (FAQ), 6 Minutes Walk Test and gait analysis (GA) parameters were recorded before and after training. Over all the patients in RDO + CP group, all GMFM domains and FAQ improved after RDO training (p < 0.05). The unaffected limb showed significantly decreased stance, increased step length and reduced anteroposterior center of pressure oscillation; the affected side increased the stride length. ROM hip and knee flex-extension increased bilaterally (p < 0.05 for all). RDO training during the acute/subacute post-injury phase increased motor functional abilities, cadence and velocity of gait (p < 0.05). We conclude that RDO imposes a proximal-to-distal differential effect on the lower limbs, with the hip joint being the most stimulated. RDO training fostered recovery, increasing the quality of gait on the unaffected side. Planning RDO early in the rehabilitation course of pediatric ABI is advantageous. RDO + CP may extend rehabilitation efficacy to the proximal segment of leg and to gait velocity. Highlights: RDO training imposes a differential proximal-to-distal recovery on the legs. RDO training primarily stimulates the hip and knee joints. RDO + CP may extend rehabilitation efficacy to gait velocity and cadence. Planning RDO early in the rehabilitation course of pediatric ABI is advantageous.